The Impact of Home Production on Economic Inequality in Germany - Joachim R. Frick; Markus M. Grabka; Olaf Groh-Samberg (Empirical Economics, 2012)
Using representative income and time-use data from the German Socio-Economic Panel, we estimate non-monetary income advantages arising from home production and analyze their impact on economic inequality. As an alternative to existing measures, we propose a predicted wage approach that relaxes some of the strong assumptions underlying both the standard opportunity cost approach and the housekeeper wage approach. We also propose a method of adjusting the number of hours spent on home production to reduce the bias arising from multi-tasking and joint production in time-use data. Sensitivity analyses comparing results among different approaches provide indications of method effects. Although this study supports the evidence that considering home production leads to a reduction in inequality, we show that the size of this effect differs according to the variations in the mean and distribution of the estimated monetary value of home production across the three approaches. This finding underscores the need for a harmonized approach in cross-national comparative research.
Additional information: The final publication is available at www.springerlink.com: http://dx.doi.org/10.1007/s00181-011-0523-7
Keywords: D31; D13; I32; 330; home production; non-cash incomes; economic inequality; well-being; SOEP; Panel